A Systematic Review on the Mechanical, Tribological, and Corrosion Properties of Al 7075 Metal Matrix Composites Fabricated through Stir Casting Process. (21st January 2023) - Sambathkumar, M.; Gukendran, R.; Mohanraj, T.; Karupannasamy, D. K.; Natarajan, N.; Christopher, David Santosh
Abstract : Aluminium alloy components are used in lightweight engineering applications and lack mechanical properties, wear resistance, and corrosion resistance. When hard reinforcement particulates are dispersed in the aluminium matrix alloy, aluminium matrix composites (AMCs) are formed. This new material exhibits enhanced properties such as better specific stiffness, specific strength, corrosion resistance, elastic modulus, wear resistance, and lightweight. AMCs have many favorable properties compared to their alloy and extensive applications. Especially, in the space industry, where weight reduction and an increase in modulus are prevalent, the strength-to-weight ratio is more important. This study focuses on the tribological, mechanical, and corrosion properties of Al 7075 metal matrix composites (MMCs) reinforced with one or more particulates such as aluminium oxide (Al2 O3 ), boron carbide (B4 C), titanium carbide (TiC), silicon carbide (SiC), titanium dioxide (TiO2 ), and titanium diboride (TiB2 ). In AMCs, the reinforcements are incorporated by either the solid or liquid metallurgy route. The study addresses the findings and shortcomings in the preparation of MMCs with reinforcements and their improvement in corrosion resistance, wear resistance, mechanical properties, and lower coefficient of thermal expansion than the Al 7075 base alloy. A comprehensive survey of reinforcement particulates in MMCs and their influences are outlined from the literature, encompassing recent research trends to enhance the structural properties.